Hotline - Intermediate (Workbook - Student's Book) - Tom Hutchinson (Oxford Univ. Press, 1993)
The book covers a lookback syllabus, a grammar-based analytical approach, skills work, project work, cross-cultural and cross-curricular studies, learner training